A COMPARATIVE STUDY BETWEEN INDONESIAN UNDERGRADUSTE AND GRADUATE STUDENTS’ PERCEIVED ANXIETY AND SELF-EFFICACY IN CRITICAL WRITING - Fidelia Ratih Widya Wardani; Concilianus Laos Mbato (Widya Mandala Surabaya Catholic University, 2021)
This study aimed to investigate students’ perception on their writing anxiety and how they employed their writing self-efficacy as well as the relationship between writing anxiety and writing efficacy. This research was conducted toward 29 students from undergraduate and graduate EFL students in Yogyakarta who were taking critical writing course. This study used mixed-method research employing a close-ended questionnaire and interview to gather the data. The writing anxiety questionnaire statements were adopted from Cheng (2004), while the writing efficacy statements were adopted from Eby (2018). The data results were analysed using SPSS version 25 then described statistically, whilst the interview data were analysed using thematic analysis. The results showed that both undergraduate and graduate students have a high self-efficacy and anxiety in writing. A correlation test was conducted and described in the discussion section to see the relationship between writing anxiety and writing efficacy indicates that all aspects of writing anxiety had a negative correlation but not significant with writing ability and behavior. However, not all aspects of writing anxiety such as somatic anxiety, avoidance behaviour, and cognitive anxiety had a negative correlation with writing ideas, writing conventions and self-regulation in writing. The interview result showed that the students who had good self-efficacy in writing felt anxiety as a means to explore themselves and foster a positive mindset to continue progressing in writing. The implication of this research is to expand knowledge related to writing practice in EFL context and educational psychology.